This lullaby - Dessen, Sarah (New York : Viking, 2002)
Raised by a mother who's had five husbands, eighteen-year-old Remy believes in short-term, no-commitment relationships until she meets Dexter, a rock band musician.
820
Accelerated Reader AR
Keywords: Interpersonal relations -- Juvenile fiction; Bands (Music) -- Juvenile fiction; Musicians -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction